Effect of elastin‐like polypeptide incorporation on the adhesion maturation of mineral trioxide aggregates. Issue 7 (3rd May 2020) - Kim, Hyun‐Jung; Lee, Wang Sik; Jeong, Jinyoung; Kim, Duck Su; Lee, Seung‐Wuk; Kim, Sun‐Young
Abstract: The aim of this study was to investigate the effects of the incorporation of elastin‐like polypeptide (ELP) on the adhesion maturation of mineral trioxide aggregates (MTA). Two types of ELPs (V125 and V125E8) were genetically synthesized. V125 consisted of 125 repeating pentapeptides (Val‐Pro‐Gly‐Xaa‐Gly) and V125E8 was functionalized with octaglutamic acid in the C‐terminus of V125; both were diluted to 10 wt% in solution. Three 1.5 mm diameter holes in dentin discs were filled with MTA mixed with either a solution of ELP or deionized water. Push‐out bond strength tests were performed following storage in simulated body fluid (SBF) for 1, 2, 4, and 8 weeks ( n = 12). The interface between dentin and MTA was observed via scanning electron microscopy (SEM). The maturation of MTA was evaluated with a stereoscopic microscope and SEM. The incorporation of a specific ELP (V125E8) significantly increased the bond strength of MTA to dentin with regard to every maturation period ( p  < 0.05). The bond strength of MTA also significantly increased with a longer maturation time irrespective of ELP incorporation ( p  < 0.05). V125E8‐incorporated MTA exhibited a more intimate interface with dentin compared to the other groups. More spindle‐shaped crystal structures and thicker crystals were observed in all MTA mixtures as the storage duration increased even though V125E8 exhibited fewer crystal structures on the surface. Within the limitations of this study, the incorporation of V125E8 increased the adhesive properties of MTA and the maturation of MTA occurred regardless of ELP incorporation.